1999
DOI: 10.1111/j.1532-5415.1999.tb04577.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risks of Dementia in the Japanese Population: RERF's Adult Health Study Hiroshima Subjects

Abstract: This study is the first study of Japanese dementia rates carried out with a protocol similar enough to that of a US study to allow meaningful comparisons. The prevalence rates demonstrated are more similar to US rates than were found in many previous reports in Japan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
96
1
5

Year Published

2001
2001
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(109 citation statements)
references
References 28 publications
7
96
1
5
Order By: Relevance
“…Clinical data on this issue are scarce and somehow contradictory. In most studies, cancer seems to be a prevalent comorbidity for patients with AD, and for males in particular (Gambassi et al, 1999;Gasper et al, 2005), although specific proportions vary from 8% (Formiga et al, 2007(Formiga et al, , 2008 to almost 23% in patients with reported exposure to carcinogens (Yamada et al, 1999). Other studies find that the risk of developing cancer, in organs distant from the central nervous system, is lower among AD patients than in nondemented patients (Beard et al, 1996;Roe et al, 2005).…”
Section: Introductionmentioning
confidence: 94%
“…Clinical data on this issue are scarce and somehow contradictory. In most studies, cancer seems to be a prevalent comorbidity for patients with AD, and for males in particular (Gambassi et al, 1999;Gasper et al, 2005), although specific proportions vary from 8% (Formiga et al, 2007(Formiga et al, , 2008 to almost 23% in patients with reported exposure to carcinogens (Yamada et al, 1999). Other studies find that the risk of developing cancer, in organs distant from the central nervous system, is lower among AD patients than in nondemented patients (Beard et al, 1996;Roe et al, 2005).…”
Section: Introductionmentioning
confidence: 94%
“…Risk factors for Data Science Journal, Volume 8, 24 September 2009 dementia were age, higher systolic blood pressure, history of stroke, history of hypertension, history of head trauma, lower milk intake, and lower education (Yamada, Sasaki, Mimori, Kasagi, Sudoh, Ikeda, et al, 1999;Yamada, Kasagi, Sasaki, Masunari, Mimori, & Suzuki, 2003). However, taking into account that increased blood pressure was the main contributor to vascular dementia (Yamada, Sasaki, Mimori, Kasagi, Sudoh, Ikeda, et al, 1999), it is important to note that in the same Adult Health Study a statistically significant effect of ionizing radiation on the longitudinal trends of both systolic and diastolic blood pressure was recently found. This phenomenon is compatible with the degenerative effect of ionizing radiation on blood vessels (Sasaki, Wong, Yamada, & Kodama, 2002).…”
Section: Epidemiological Datamentioning
confidence: 99%
“…Cardiovascular disease is one such non-cancer disease for which increases in both mortality and incidence have been found to be associated with radiation dose (Kusunoki, Kyoizumi, Yamaoka, Kasagi, & Kodama, 1999). The recognition in atomic-bomb survivors of non-cancer effects at doses on the order of 0.5 Sv (half the dose level considered a threshold in earlier studies) should stimulate interest in deterministic effects (Shimizu, Pierce, Preston, & Mabuchi, 1999;Fry, 2001;Preston, Shimizu, Pierce, Suyama, & Mabuchi, 2003) and non-cancer morbidity and mortality following the Chernobyl accident.…”
Section: Epidemiological Datamentioning
confidence: 99%
“…According to epidemiological research in Japan, the prevalence of dementia is 7.2% in people aged 60 years and older and 8.5% in people ages 65 years and older (3,4). In this situation, an extension of life span per se is no longer the goal of the elderly, an improvement in functional independence and the achievement of a better quality of life (QOL) being more important.…”
Section: Introductionmentioning
confidence: 99%